Improving Critical Thinking Skills through a STEAM-Integrated SSCS Learning Model on Static Fluid Concepts - Iljannah, Luk Luk; Parno, Parno; Sujito, Sujito; Nawi, Nina Diana (Department of Physics Education, Universitas Mataram, 2025)
Critical thinking skills in static fluid materials remains suboptimal, necessitating the implementation of an instructional model that effectively enhances this skill. The STEAM-integrated SSCS learning model presents a novel solution that is still rarely applied in educational settings. This study aims to examine the effect of this model on improving students' critical thinking skills in static fluid materials. A quasi-experimental design with a Pretest-Posttest Control Group was employed, involving Class XI students from SMA Negeri 1 Boyolangu Tulungagung. Participants were selected using a cluster random sampling technique, comprising 37 students in the experimental class (STEAM-integrated SSCS model) and 34 students in the control class (conventional model). The instrument used was a Critical Thinking Skills Test on static fluid material, consisting of nine essay questions validated with a reliability coefficient of 0.625 (medium category). The analysis revealed that the STEAM-integrated SSCS model significantly improved students' critical thinking skills, as indicated by a significance value of 0.000. The experimental class obtained an N-Gain score of 0.678 (medium category), higher than the control class's score of 0.426 (medium category). N-Gain values for each static fluid submatter and critical thinking indicator were also consistently higher in the experimental class. Although improvements were observed, experimental class students still faced difficulties in problem-solving and decision-making, while control class students struggled with hypothesis testing. The model's effectiveness is further supported by a Cohen's d effect size of 1.997, categorized as “large”. Future research should consider optimizing the learning time to complete the miniature products and increasing the number of pre-test and post-test items to allow for more comprehensive analysis of each submatter and could explore the application of STEAM-integrated SSCS across various physics topics to verify generalizability.